Exploração contextual de fórmulas matemáticas na web para pessoas com deficiência visual em leitor de telas de código aberto - Guedes, Hérlon Manollo Cândido (2020)
The evolution of technological resources has expanded access to information for everyone, especially for people with disabilities. For this reason, the availability of digital teaching content such as e-books, PDFs, and Web content has broadened access to knowledge. However, some barriers persist concerning the access of people with visual disability to information. Even with technological advances and the availability of various materials in digital channels that can be read out by screen readers, specific contents such as mathematics are still a problem for users of these systems. Due to the complexity of mathematical notations and their abstract nature, mathematics is a science that presents challenges for understanding by means other than visual. Thus, reading mathematical content using screen readers currently faces problems such as ambiguity, helping to understand long formulas, and identifying specific elements. Besides, even with reading problems, few screen readers support reading this type of content. The situation is even more difficult considering screen-reader support for Portuguese reading, with a total absence of support in commercial and free widely-used screen readers. Understanding the reading of formulas through TTS systems still presents challenges. The lack of possibility of obtaining an overview of the contents and the limitation of the sequential nature of speech synthesis are problems that make understanding difficult. Thus, this study aimed to implement and evaluate a plugin for reading and to explore mathematical formulas with NVDA. This way, the plugin presented here offers the ability to internally explore the formulas using contextual delineations in mathematical elements with support to the Brazilian variant of the Portuguese language. For this, this study was based on results of previous works that had the participation of the author of this dissertation, which involved: interviews with 12 people with visual disabilities, in addition to conducting tests on a prototype based on the ChromeVox screen reader, including the participation of five people with visual disability. From the identification of users’ needs and through interviews and tests using the ChromeVox-NavMatBR prototype, problems were identified involving memory overload and ambiguous understanding of mathematical formulas. Bearing these problems in mind, we present here a plugin with Brazilian Portuguese narration, called Access8Math-NavMatBR. This new plugin was based on the open-source Access8Math plugin. The version of the plugin was developed and evaluated in usability tests with the participation of six people with visual disabilities. Tests with the new system demonstrated an improvement in the understanding of formulas and an improvement in access to specific elements with exploration with an abstraction of formulas. The system showed to be a crucial technological contribution, as it is a plugin with free distribution for use. As a scientific contribution, we present advances in the study of techniques to help the understanding of mathematical formulas by people with visual disability through screen readers. As it is an open-source system, the work also allows its use in future researches. This work also brings scientific contributions to a better understanding of the needs of screen reader users. Besides, it presents design implications for systems for reading mathematical formulas in the Brazilian context. This work also brings considerations on the exploitation patterns used by Brazilian users in regards to reading and browsing mathematical formulas.